The Effect of Leadership Style to Employee Work Motivation on Technology Start-Up in Entrepreneurship Student: A Case Study in Sini Company (Journal of Innovation, Business and Entrepreneurship, 2020)
Sini is a start-up that run-in technology industry especially device tracker. In addition to device tracker, they also sell complementary products such as wallets, key chains and passport cases. The problem is the internal relationship in the company is less harmonious, so the members feel demotivated. They expressed demotivated because of the leader's actions. Therefore, the author analyzes the type of leadership style from Sini Company and what its effect is to member motivation. Author uses qualitative development methods namely phenomena and study cases from Sini Company. The method of data collection used by author is with leadership assessment, observation, interview and focus group discussion. From the assessment leadership style obtained result of autocratic leadership style. The autocratic leadership style is a style of leadership that is nudge controlling its members and less involving its members in an important matter such as decision making. To find out the relationship between leadership style and motivation of Sini Company members, author uses internal and external motivation framework. The internal factor consists of recognition, achievement, possibility to growth and advancement, and the work itself. For the external factor, consist of supervision, salary provided and company rules. From the factors, there will be find the factors that make the members demotivated.Keywords: autocratic, demotivated, external motivation, internal motivation, leadership style, start-up.